Combination of CAKUT-syndrome and axial skeletal abnormalities - O. A. Kaplunova; E. V. Chaplygina; M. M. Batiushin; O. P. Sukhanova; I. M. Blinov; E. D. Stefanova; A. M. Batiushina (Вестник урологии)
Combined anomalies of the urinary system and axial skeleton, including an L-shaped kidney, obstruction of the ureteropelvic junction (CAKUT syndrome, congenital anomalies of the kidney and urinary tract syndrome) and spinal anomalies, are extremely rare. The clinical case gives a description of a similar combined developmental anomaly.